Rabies in the Republic of Kazakhstan: spatial and temporal characteristics of disease spread over one decade (2013–2022) - Kabzhanova, Anar M.; Kadyrov, Ablaikhan S.; Mukhanbetkaliyeva, Aizada A.; Yessembekova, Gulzhan N.; Mukhanbetkaliyev, Yersin Y.; Korennoy, Fedor I.; Perez, Andres M.; Abdrakhmanov, Sarsenbay K. (Frontiers in Veterinary Science, 2023)
Rabies is a fatal zoonotic disease that remains endemic in Kazakhstan despite the imple-17 mentation of annual vaccination campaigns. Using data collected over a 10-year time period, the 18 objective of this study was to provide updated information on the epidemiological situation of the 19 disease in the country, and quantitative data on the species-specific spatial distribution of rabies and 20 on the epidemiological features associated with that clustering. Five significant (P<0.05) clusters of 21 disease were detected. Clusters in southern Kazakhstan were associated with companion animals, 22 which are likely explained by the maintenance of a domestic cycle of the disease in the most densely 23 populated region of the country. Livestock cases were most frequent in clusters in the eastern (where 24 wildlife cases were also frequent) and western regions of Kazakhstan, with higher probability of 25 occurrence in spring and summer, compared to the rest of the year. The results here are consistent 26 with differential patterns for disease transmission in Kazakhstan and will contribute to the design 27 and implementation of zoning approaches to support the progressive control of rabies in the coun-28 try.